(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Traditionally, women were considered the caretakers of home. They had to look after the running of the family smoothly, they have to manage the expense in the economical way possible, they had to look after aged in-laws, nature the child, et They were expected to obey orders of their husband, the elders of the family, but kept in isolation when it came to major decision related to the family. The women were not too educated in the past eras They would be named off one day to their laws place and hence would not need too much knowledge was the previous thinking. There were women in older days too, who were well educated and led paths of success in many sphere of life, because of support from their families. It is these women who lead paths of change and brought about a transformation in the way people viewed women in the society